Personalized Treatment of Heart Failure with Biomarker Guidance Using a Novel Disease Severity Score. Issue 2 (1st April 2017) - Vasudevan, Anupama; Jazi, Hourossadat Hashemi; Won, Jane I.; Ball, Timothy; Patankar, Gautam R.; Sarmast, Syed A.; Shin, Hyun Joon; Mccullough, Peter A.
Abstract : We propose a novel Myocardial Injury Summary Score (MISS) integrating the 4 biomarkers suggested by the 2013 American College of Cardiology/American Heart Association guidelines for management of heart failure. In this case series, we examined 4 heart failure patients who received treatment guided by the biomarker results and 4 patients who received routine clinical management with no information about the biomarkers. Most of the patients receiving biomarker-guided management had medications adjusted based on the biomarker values, while no changes were recommended for patients in the biomarker-blinded category. This case series suggests that biomarker-guided therapy with serial biomarker values leads to timely therapeutic adjustment and that biomarker values as a composite score can be used effectively to measure the severity of heart failure.